(untitled) (Swiss Medical Weekly, 2026)
AIMS OF THE STUDY: Marketing authorisation of the bivalent respiratory syncytial virus prefusion F protein-based vaccine (RSVpreF) for maternal vaccination was predominantly based on safety and efficacy findings from the pivotal global phase 3 Maternal Immunization Study for Safety and Efficacy (MATISSE) trial that included >7000 pregnant women and their infants. The aim of this post hoc analysis was to evaluate clinical efficacy and safety endpoints within the subgroup of participants from the MATISSE trial who received RSVpreF or placebo at 32−36 weeks of gestation, which is the indicated gestational age (GA) window for maternal RSVpreF vaccination in Switzerland. METHODS: Healthy pregnant women ≤49 years of age with uncomplicated, singleton pregnancies were randomised 1:1 to receive a single dose of RSVpreF 120 μg or placebo. Primary efficacy endpoints were vaccine efficacy against severe medically attended RSV-associated lower respiratory tract illness and medically attended RSV-associated lower respiratory tract illness in infants occurring within 90 and 180 days after birth. This is a descriptive post hoc analysis of efficacy and safety endpoints from MATISSE among the subgroup of newborns whose mothers received RSVpreF or placebo at 32–36 weeks of gestation. RESULTS: Of 7392 maternal participants included in the primary MATISSE analysis, 3285 (RSVpreF: 1653; placebo: 1632) received vaccination at a GA of 32–36 weeks and were included in this analysis. Efficacy was evaluated in a total of 1628 and 1604 infants who were born to mothers receiving RSVpreF or placebo, respectively. RSVpreF vaccine efficacy percentages against severe medically attended RSV-associated lower respiratory tract illness were 91.1% (95% CI: 38.8–99.8%) and 76.5% (95% CI: 41.3–92.1%) within 90 and 180 days of birth, respectively. RSVpreF vaccine efficacy percentages against medically attended RSV-associated lower respiratory tract illness were 34.7% (95% CI: –34.6–69.3%) and 57.3% (95% CI: 29.8–74.7%) within 90 and 180 days of birth, respectively. Adverse event profiles for maternal and infant participants were generally similar between RSVpreF and placebo groups in this post hoc analysis; safety results were consistent with those of the primary and final analyses. CONCLUSIONS: Maternal vaccination with RSVpreF in pregnant women at 32−36 weeks of gestation is safe and efficacious against RSV-associated lower respiratory tract illness in infants to 6 months of age, aligning with the outcomes of the primary analysis. ClinicalTrials.gov: NCT04424316